Determining the Impact Bruising of Goji Berry Using a Pendulum Method - Yanwu Jiang; Qingyu Chen; Naishuo Wei (Horticulturae)
Lycium barbarum L. (goji), as an economic crop, has a high added value. However, the tender and fragile fruits are easily damaged during harvesting and transportation, leading to fruit bruising, which can cause rotting or black–brown spots after drying, seriously affecting the quality and price. In this study, two varieties of goji were used to determine and evaluate fruit bruising using a pendulum impact test, and the impact process was recorded using a high-speed camera and impact force sensor. This study discussed the energy changes during the impact process of fruits and conducted a correlation analysis of the impact energy, absorbed energy, restitution coefficient, impact force, and other indicators, analyzing the changes in each indicator with the falling height. The results showed that 0.2 m could be considered a critical height for damaging the fruit of goji. Furthermore, this study calculated the bruise susceptibility of the different varieties at different heights, which can be used for predicting bruising during the harvesting and collection of goji berries and ultimately for estimating the damage caused by mechanical harvesting.